Development of a Lentiviral Reporter System for In Vitro Reprogramming of Astrocytes to Neuronal Precursors - Anna Schnaubelt; Guoli Zheng; Maryam Hatami; Johannes Tödt; Hao Wang; Thomas Skutella; Andreas Unterberg; Klaus Zweckberger; Alexander Younsi (Biology)
Astrocytes, which proliferate after brain injury, represent a promising target for cellular reprogramming due to their abundance and ability to support brain repair. In this study, we investigated the in vitro reprogramming of primary cortical astrocytes from neonatal rats into neuronal precursor cells (NPCs) using the transcription factors Oct4, Sox2, and Klf4 (OSK), delivered via lentiviral vectors. We designed a reporter system to trace the conversion of astrocytes to NPCs and neurons by using GFAP-driven iCre and Nestin- or Synapsin1-driven fluorescent reporters. After transduction, we observed morphological changes and the expression of neuronal markers in some cells, while many cells remained in a transitional state, expressing both astrocytic and neuronal features. Importantly, the study was not designed to quantify reprogramming efficiency or demonstrate full astrocyte-to-neuron conversion but rather to establish and evaluate a traceable reporter system. Our data suggest that OSK-mediated reprogramming in this in vitro model can initiate conversion of astrocytes to neuronal precursor-like cells, although the process is complex and incomplete within the one-week timeframe. We also highlight limitations in co-transduction efficiency and potential silencing of the reporter system during reprogramming. These findings provide an initial technical platform to explore astrocyte reprogramming in vitro and inform future studies aiming to refine these methods and apply them in vivo.